PENYELENGGARAN REKRUTMEN PEGAWAI DI YAYASAN INSPIRASI PEMBELAJAR - Rio Friyadi; Zulfani Sesmiarni (CV. Adiba Aisha Amira, 2025)
Organizing Employee Recruitment at the Insprasi Learner Foundation is an educational institution that is committed to providing quality educational services for students and the community. In this eflort, educational institutions need good public relations management to build a positive image, expand cooperation networks, and increase community participation in educational activities. In this article, we discuss the main functions of educational public relations management according to experts and the importance of public relations management in the implementation of education. We also reviewed the implementation of public relations management carried out by the Learner Inspiration Foundation, starting from planning, implementation, to evaluation. This evaluation includes customer satisfaction evaluation, employee performance evaluation, learning program evaluation, and social activity evaluation. By conducting regular evaluations, existing deficiencies can be corrected and the quality of educational services provided to students and the community can be improved.